District nurses' experiences of preventive home visits to 75-year-olds in Stockholm: a qualitative study. Issue 5 (1st December 2015) - Lagerin, Annica; Törnkvist, Lena; Hylander, Ingrid
Abstract : Aims: This study had two aims: to describe the dialogue between district nurses (DNs) and older people in preventive home visits (PHVs) from the perspective of the DNs, and to identify barriers to and facilitators of this dialogue as perceived by the DNs. Background: The number of older people is rapidly increasing in all western countries, and as people's age increases, the probability that they will have multiple diseases also increases. Planned actions are therefore needed to promote health and prevent diseases among older people so they can remain in good health and live in their homes for as long as possible. In Sweden, PHVs to 75-year-olds by DNs are one such action. Methods: This qualitative study included five group interviews with 20 DNs. Data were analysed with qualitative content analysis. Findings: DNs' experiences of barriers to and facilitators of a successful health dialogue were sorted into five domains. Together, these domains provided a systematic description of the interaction between the DN and the older person in the PHV. The domains included: establishing trustful contact, conducting a structured interview, making an overall assessment, proposing health-promoting activities and offering follow-up. The barriers and facilitators could be related to the older person, the DN or the home environment. The latent content of the interviews was evident in three themes that were related to the DNs' experiences of barriers and facilitators. These themes illustrated professional dilemmas that the DNs had to resolve to achieve the purpose of the PHV. The study demonstrates that the interaction between a DN and an older person in a PHV can be described as a complex social process in which the DN balances a personal and professional approach, combines a person-oriented and a task-oriented approach and employs both a salutogenic and pathogenic perspective.